Den lige linje i Grundtvigs religiøse udvikling - Rod, Jakob (Grundtvig-studier, 1970)
“ The Direct Line in Grundtvig’s Religious Development By Jakob Rod Grundtvig’s religious development is largely influenced by crises, sudden realisations of “crystal clear” truths and breaks with the past. But this does not imply that there is no coherence. On the contrary there is a direct line in his religious development from his childhood, through his youth, and to his mature years.The writer attempts to reveal this line by bringing to light autobiographical features from Grundtvig’s writings. Attention is focused not so much upon Grundtvig’s theological opinions as upon his emotional attitude to religion. This latter is regarded as a constituent factor not only of his religious attitude, but to a certain extent also of his opinions.The various religious crises are explained as results of a repression of emotional life in his childhood and youth. Grundtvig’s inner struggle is accordingly seen as a struggle towards a form of Christianity in which his emotional life could assert itself. His emotional demands, as they appear, even during crises, show that Grundtvig’s development, hidden behind his changing opinions, always points towards a single goal: the rebirth of the faith of his childhood in a mature form.